Acceptability of patient reported outcome measures (PROMs) in a cystic fibrosis data registry. Issue 1 (19th July 2021) - Ratnayake, Irushi; Ahern, Susannah; Ruseckaite, Rasa
Abstract : Introduction: Improvements in the treatment of cystic fibrosis (CF) have resulted in longer survival and an increased focus on optimising daily functioning with the condition. Patient-reported outcome measures (PROMs) are valuable tools in evaluating the health-related quality of life of persons with chronic diseases. PROMs may be incorporated into clinical registries to assess and provide feedback regarding the health-related quality of life of the affected population. This study uses qualitative methodology to describe the views of patients with CF, caregivers and clinicians on the usefulness and practicality of incorporating a PROM in the Australian Cystic Fibrosis Data Registry (ACFDR). Methods: We conducted semistructured interviews with a convenience sample of patients with CF (n=5), caregivers (n=7) and clinicians (n=13) on their opinions on incorporating the Cystic Fibrosis Questionnaire-Revised or the Cystic Fibrosis Quality of Life Questionnaire into the ACFDR. We analysed data into topics and subtopics using conventional content analysis. Results: Participants believed that PROMs could generate useful aggregate health-related quality of life data to support better understanding of the experiences of the modern CF population. Participants emphasised that implementation must be supported by processes to feedback data to patients and clinicians. Most participants preferred electronic PROMs administration for easy integration into existing systems and the potential to support feedback. Conclusion: Patients, caregivers and clinicians in this study generally supported the usefulness and practicality of PROM implementation in the ACFDR.